THE EFFECT OF SCHOOL ENVIRONMENT, THE ROLE OF TEACHERS IN LEARNING PROCESS TO STUDENT LEARNING MOTIVATION - Citra Ayu (Journal of English Language and Education, 2017)
Education is one of the most important things to prepare for future success in the era of globalization. Education can be achieved in various ways one of which schooling. According Suharsimi Arikunto (1997: 4) states that the education process there are five factors that affect the: (1) teachers and other personnel, (2) material, (3) methods of teaching and evaluation system, (4) a means of supporting and ( 5) administration system. The fifth factor in the school environment. Motivation is a condition which is owned by each student to bertingah behavior. According W.S. Winkel (1983: 29) students were already seated at SMA / SMK should be more influenced by intrinsic motivation, because the student already has awareness of the importance of learning for the future. But in reality there are still many students who have not been influenced by the intrinsic motivation. Based on these things, so that teachers have an important role to develop the intrinsic motivation. The motivation of every student was different, especially in terms of learning motivation is often called the motivation to learn.